The Capital Structure Theory as It Relates to The Food Sector. A Developing Economy's Evidence - Chikwira , Collin (Dinasti International Journal of Economics, Finance & Accounting, 2023)
The study's objective was to investigate the capital structure theory in the food industry, focusing on manufacturing companies listed in Zimbabwe. By looking at these companies' capital structures, we aimed to pinpoint the factors influencing capital structure decisions in the food industry and provide managerial implications for businesses operating in this market. From 2017 to 2022, the study used Panel data from the financial statements of manufacturing companies listed on the Zimbabwe Stock Exchange and Victoria Falls Stock Exchange. The findings demonstrate the importance of business value and capital structure despite their negative relationships. For a variety of stakeholders, the study has value implications. This study offers managers in the food business insights into the variables influencing firms' capital structures, empowering them to make educated decisions about their financing options. The study can also be used by investors in this industry to assess the capital structure of businesses they are considering investing in, which will ultimately help them make more educated choices. Additionally, policymakers can use the study's findings to create policies that support the expansion and development of Zimbabwe's food business, thereby boosting that nation's economy.